Effectiveness of community-based multidisciplinary integrated care for older people: a protocol for a systematic review - Liam Glynn; Rose Galvin; Katie Robinson; Margaret O'Connor; Elaine Shanahan; Christina Hayes; Molly Manning; Brian Condon; Anne Christina Griffin; Christine FitzGerald (BMJ Open, 2022)
Introduction The increasing number of older adults with multiple complex care needs has placed increased pressure on healthcare systems internationally to reorientate healthcare delivery. For many older adults, their first point of contact with the health service is with their general practitioner (GP) and GP participation with integrated care models is the foundation of a population-based approach. A knowledge gap remains in relation to the effectiveness of GP participation in community-based integrated health and social care approaches for older adults. This systematic review aims to examine the effectiveness of multidisciplinary-integrated care for community-dwelling older adults with GP participation.Methods and analysis This systematic review will include randomised controlled trials (RCTs), quasi and cluster RCTs focusing on integrated care interventions for community-dwelling older adults by multidisciplinary teams including health and social care professionals and GPs. The databases PUBMED, EMBASE, CINAHL, Central Register of Controlled Trials in the Cochrane Library and MEDLINE will be searched. The primary outcome measure will be functional status. Secondary outcomes will include: primary healthcare utilisation, secondary healthcare utilisation, participant satisfaction with care, health-related quality of life, nursing home admission and mortality. The methodological quality of the studies will be assessed using the Cochrane Risk of Bias Tool V.2. The elements of care integration will be mapped in the individual studies using the Rainbow Model of Integrated Care taxonomy. A meta-analysis will be completed, depending on the uniformity of the data. Grading of Recommendations, Assessment, Development and Evaluation will be used to assess the certainty of evidence.Ethics and dissemination Formal ethical approval is not required as all data included are anonymous secondary data. Scientific outputs will be presented at relevant conferences and in collaboration with our public and patient involvement stakeholder panel of older adults at the Ageing Research Centre at the University of Limerick.PROSPERO registration number CRD42022309744.